Analisis struktur dan sumber pertumbuhan ekonomi Provinsi Jambi - Diano, Meka; Amir , Amri; Zulgani, Zulgani (Jurnal Paradigma Ekonomika, 2024)
The objectives of this study are 1) To analyze the economic structure of Jambi Province in terms of the structure of demand and supply. 2) Analyze the influence of production factors on the economic growth of Jambi Province. The analytical tool used is the analysis of the economic structure of the supply and demand approach as well as multiple linear regression. Based on the research results, during 2010 to 2019 it turns out that the primary sector has always had a positive and greater impact than the industrial sector and the service sector on economic growth in Jambi Province. These results also show that the contribution of the industrial sector always shows a decline in economic growth, while the primary and service sectors only show fluctuating growth. Then during 2010 to 2019 the proportion of consumption (C) was very large, namely 45.84 percent, followed by investment, then investment (I) the proportion was 23.2 percent, government spending (G) the proportion was only 8.07 percent and exports -import (xm) the proportion is 22.89 percent. Furthermore, the contribution of the production sector to economic growth in Jambi Province was contributed by technology with a contribution to economic growth of 50.65 percent, followed by a contribution of capital / investment of 25.92 percent and labor contributed 23.43 percent to economic growth.